ASSISTIVE TECHNOLOGIES AND PEDAGOGICAL INNOVATION: TOOLS FOR EFFECTIVE INCLUSION - de Oliveira, Ricardo Cesar; Sobral, Emanuela Almeida; Queiroz, Francisca Brena Silva; do Nascimento, Eliana Almeida; Vilarva, Nívea Maria Lopes; Gonçalves, Victor Linhares (Editora Impacto Científico, 2025)
The debate on assistive technologies in the educational field has gained increasing relevance, especially in the context of discussions on pedagogical innovation and effective inclusion. The school, as a space for the collective construction of knowledge, faces the challenge of ensuring learning conditions for all students, regardless of their physical, sensory, or cognitive limitations. In this sense, assistive technologies are configured as instruments capable of mediating students’ active participation, expanding their autonomy, and fostering equity of opportunities in the school environment. According to Bersch (2017), such technologies should not be seen merely as technical resources, but as elements that enhance communication, expression, and access to information. This view dialogues with Freire’s perspective (1996), for whom the educational process requires the appreciation of human diversity and the creation of conditions that ensure inclusion as a democratic practice. At the same time, the integration of digital tools into the school routine, when guided by consistent pedagogical principles, enables innovation in teaching practice and in the way knowledge is produced and shared. Authors such as Moran (2018) emphasize that pedagogical innovation is not limited to the adoption of new technologies but involves the transformation of methodologies and the pursuit of more meaningful learning. Thus, the presence of assistive technologies in the classroom demands planning, teacher training, and public policies that favor their implementation. More than a punctual resource, it represents a path to consolidate an inclusive culture that recognizes difference as a fundamental part of the educational process. Therefore, the combination of assistive technologies and pedagogical innovation can be understood as a vital strategy to make the school a space of belonging, participation, and social justice, reinforcing the commitment to a truly inclusive education.DOI: https://doi.org/10.56238/edimpacto2025.092-001